The Analysis Study of Prevalence, Diagnosis and Management of Bacterial Vaginosis: A Comprehensive Systematic Review - Porosi, Arini Nadin Litsyawardani; Putri, Amalia (International Medical Journal Corp. Ltd, 2024)
Background: Bacterial vaginosis (BV) is a prevalent condition among women of reproductive age, characterized by a disruption in the normal vaginal microbiota. The systematic review focused on analyzing the prevalence, diagnosis, and management of Bacterial vaginosis based on literature from the past decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 630 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Bacterial vaginosis remains a complex condition influenced by microbial diversity, contraceptive use, and co-infections. Improved diagnostic methods and innovative treatment strategies, including probiotics, are essential for effective management and prevention of BV and its associated complications.